The Effect Of Using Pirie And Kieran’s Model To Acquire Concepts At The First Year Intermediate Female Students In Mathematics - Al-Qadir Al chalabi, Faeeza Abd; Khazaal Al-saadi, Rafah Riyadh (Opción, 2019)
The research sample consisted of (54) female students of the first grade average, for the second semester of the academic year (2019-2018) m, Masra Rasoul Girls School of the Directorate of Education first Rusafa in Baghdad was chosen intentionally, by (28) students in the experimental group The two groups were rewarded in the following variables (intelligence, chronological age, previous information in mathematics, previous mathematics achieve- ment, and educational level of parents).